The effectiveness of different training programs in reducing body weight - Dollah, Siti Norshuhada (Universiti Sains Malaysia, 2014)
The purpose of this study was to determine the type of exercise which was effective in reducing body weight. A total of 36 overweight (BMI >25) and sedentary female subject from Universiti Sains Malaysia’s students (Health Campus) age range between 20 to 25 years old were divided randomly into Strength Training Group (n=7), Endurance Training Group (n=10), Combine Training Group (n=7) and Control Group (n=12) with median of Body Mass Index (BMI) of 33.6 kg/m2, 30.55 kg/m2, 27.90 kg/m2 and 31.50 kg/m2 respectively. During 8 weeks of intervention period, Strength Training Group (ST) participated in the intervention program of body weight strength training for 8 weeks, Endurance Training Group (ET) participated in the intervention program of aerobic exercise training type such as jogging, brisk walking and stair climbing for 8 weeks, Combine Training Group (SET) participated in both strength and endurance training exercise alternately also for 8 weeks and Control Group (C) had their owns activities. All training program exercise protocol was to perform 60 minutes of exercise 3 days per weeks. Each session included 5 to 10 minutes of warm-up and cooldown. Strength training program included; push-ups, darts, prone plank, hip-ups, sit-ups, dips, arm circles and lunges. After 8 weeks, all subjects underwent post-test to measure their body composition. The finding revealed that, engage in 8 weeks of any exercise training resulted in significant changes of body weight (p<0.05). Besides, ST group show significant changes in waist circumferences and SET group show significant change in hip circumferences. The results show that exercise training program does bring benefits in reducing body weight among overweight and obese female student (BMI > 25).